Konsep Mubazir dalam Al-Qur’an: Studi Tafsir Maudhu’i - Dadan Rusmana; Muhammad Hasan Ali (Jurnal Riset Agama, 2021)
Everyone must have got the measure of sustenance from Allah swt.. However, sometimes some of them subconsciously invest in unnecessary material possessions. The study would be exploring the concept of superfluous in the qur'an. Research methods used are a qualitative kind through library studies with content analysis. The final outcome about the discussions of this research will mentions a general view of waste, a verse about superfluous in the qur'an, and useless analysis of the verse. The final conclusion of this study represent that it is costly to waste, and these waste forms could include possessions, food, drink, and excessive use of other necessities. There are several ways to avoid the wasteful behavior given by clerics. The study recommends the importance of avoiding wasteful behavior so that avoid the harmful effects of being a brother to devil.